A SKOPOS-THEORETICAL ANALYSIS OF PROVERBS TRANSLATION IN CHINUA ACHEBE’S THINGS FALL APART INTO EKEGUSII - ONDITI, Robert; MUDOGO, Benard; BARASA, David (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This paper investigates the application of Skopos Theory in the translation of proverbs in Chinua Achebe’s Things Fall Apart into Ekegusii. The study is grounded in functionalist translation principles, and examines how target‐oriented strategies are employed to balance fidelity to the source text’s pragmatic force with cultural accessibility for Ekegusii readers. A descriptive qualitative design was adopted. A corpus of eight proverbs was extracted from the original English text, and their Ekegusii equivalents were analysed according to Skopos‐guided parameters. These are: purpose, audience, situational context and loyalty to the source text. Perspectives from Ekegusii native respondents were obtained through organised interviews on the resonance of the translated proverbs within Ekegusii cultural context. The findings reveal that majority of the proverbs were literally rendered resulting in pragmatic mismatches. However, in some instances the application of a Skopos‐oriented approach facilitated a functional and cultural coherence in translating proverbs into Ekegusii. This study underscores the necessity of target‐language awareness in cross‐cultural literary transfers